Maintenance policies for enhancing system sustainability via the delay time model - SANTOS, Augusto César de Jesus (2022)
Although there are many maintenance models and policies that have been developed in the literature of reliability engineering, most take a purely economic perspective and very few consider the environmental aspect of sustainability. Models based on the delay time concept, for instance, have been widely applied in the development of maintenance policies for systems with at least one defective state prior to the failure. However, the environmental perspective is generally not taken into account in the modelling, which represents a significant gap in the literature. In addition, new environmental legislation encourages the reuse of components and products. In this context, this thesis develops novel maintenance policies to address the need for the reuse of items through delay time modelling. From a theoretical point of view, the novelty lies in the idea of repairing defective items for reuse, to avoid the acquisition of a new item and therefore of reducing relevant economic costs, industrial waste, and a negative environmental impact. To this end, the thesis proposes methods for determining the maximum level of the defective state for items to be reused and the proportion of items to be reused in the long term, depending on the reliability levels of new and reused items. These considerations in the development of new models make it possible to verify the potential for economic and environmental improvement in contrast with traditional models that do not consider reuse and that simply replace a failed item with a new one. From a practical perspective, the thesis creates novelty by proposing a method of mitigating the problem of generating waste from the disposal of items and equipment. The contribution of this thesis is highlighted in two ways: the expansion of the delay time model beyond the economic perspective that is traditionally considered and the possibility of mitigating a considerably important problem in the industrial segment. In terms of sustainability, the economic impact refers to the considerable reduction in the maintenance cost of certain systems due to component reuse. The environmental impact is linked to the possibility of reducing the volume of industrial components that are disposed of. The social impact is related to the discussion that the social dimension should be incorporated in maintenance models and policies.